Ovarian Fibroma with Serous Cystadenoma—An Unusual Combination: A Case Report. (16th July 2012) - Jayalakshmy, P. S.; Poothiode, Usha; Krishna, G.; Jayalakshmy, P. L.
Abstract : Surface epithelial tumors account for more than 90% of ovarian tumors, of which serous tumors comprise 46%. Sex-cord stromal tumors constitute 8% of ovarian tumors, fibroma being the commonest, comprising 70% in this category. Combination of different types of tumors can occur in ovary with most common being Mucinous cystadenoma and Brenner tumour. We report a case of a very rare combination of ovarian tumour-Fibroma with Serous cystadenoma of the ovary. This combination is not mentioned in any standard textbooks or reference books of gynaecologic pathology. Extensive search of the English Literature showed only one reported case with this combination of ovarian tumors. To the best of our knowledge, this is the second case to be reported in English Literature.